2023
DOI: 10.1007/s40520-023-02389-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-domain lifestyle intervention in older adults after myocardial infarction: rationale and design of the PIpELINe randomized clinical trial

Abstract: Background Traditional cardiac rehabilitation (CR) is effective in improving physical performance and prognosis after myocardial infarction (MI). Anyway, it is not consistently recommended to older adults, and its attendance rate is low. Previous studies suggested that alternative, early and tailored exercise interventions are feasible and effective in improving physical performance in older MI patients. Anyway, the demonstration that they are associated also with a significant reduction of hard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Some studies suggested that exercise intervention is feasible and effective in older patients with MI. 18,19 Whether the combination of complete revascularization and exercise training may further improve the clinical outcomes should be demonstrated by future studies. Finally, it should be noted that complete revascularization was guided by coronary physiology and with the implantation of sirolimus-eluting biodegradable-polymer ultrathin stents (Supraflex Cruz and Sahajanand Medical Technologies Ltd).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Some studies suggested that exercise intervention is feasible and effective in older patients with MI. 18,19 Whether the combination of complete revascularization and exercise training may further improve the clinical outcomes should be demonstrated by future studies. Finally, it should be noted that complete revascularization was guided by coronary physiology and with the implantation of sirolimus-eluting biodegradable-polymer ultrathin stents (Supraflex Cruz and Sahajanand Medical Technologies Ltd).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The intervention is tailored for each patient and factors in their nutritional requirements and level of physical performance. 10 …”
mentioning
confidence: 99%